(untitled) (Communications in Mathematical Research, 2020)
In this paper, by using the coincidence degree theory, the existence of solutions for a coupled system of fractional p-Laplacian differential equations at resonance is studied. The result obtained in this paper extends some known results. An example is given to illustrate our result.